Листи А. Димінського до О. Кістяківського - Шалак, О. (Народна творчість та етнографія, 2007)
Andriy Dyminsky devoted his life to collecting folklore, his personal recordings are bigger than archives of most collectors from the 19th century, but unfortunately his name was unfairly forgotten and his contemporaries often underestimated him. This article gives some biographical information about Dyminsky’s life, financial crisis through which he lived, describes works written about him (for instance, M.Levchenko’s articles) and his collections (during his life he collected approximately 3000 songs, 700 prosaic texts, wrote some articles and essays, some of which were lost during the Civil War). At the same time the author of this article concentrates her attention mainly on the correspondence between A.Dyminsky and a lawyer, professor of the criminal law in Kyiv University O.Kistyakivsky. Additionally she publishes the letters themselves, which give an idea about A.Dyminsky’s life and attitudes toward village life style, and lives of certain people, as well as his understanding of the villagers’ layout and traditions.